A Critical Review of the Market Efficiency Concept - Mustafa, Karwan Hussein; Ahmed, Amanj Mohamed (IAIN Surakarta, 2020)
The market efficiency hypothesis has attracted a notable number of economists to conduct investigations in this field. It could be considered as an effective method of driving investors towards the right direction while trading in the security market. A large number of researches believe that the market is efficient in some of its forms, while others take a different view. Drawing on previous theoretical and empirical studies investigating market efficiency and its three forms, this paper critically examines the concept of market efficiency through a critical review from different points of views. Moreover, it highlights a number of empirical tests and their results with regard to the three forms of market efficiency. It also focuses on the influence of market efficiency on the security prices. This paper concludes that the market seems to be more efficient in regards to its weak form instead of the strong and semi- strong forms, as a result, it is difficult to predict future security prices and obtain abnormal profits by only analyzing historical records.